Modulating the coordination environment of Co single-atom catalysts: impact on lithium-sulfur battery performance - Li, Yi (2024)
The coordination environment is crucial to the electrocatalytic activity of single-atom catalysts (SACs). Although substituting N atoms in traditional transition metal-nitrogen (TM-N4) configuration with other non-metal atoms has been reported, its specific role in sulfur electrochemical reactions has not been sufficiently investigated. Herein, a Co-P2N2 SACs configuration is fabricated to investigate the mechanistic differences compared to Co-N4 in sulfur reduction/oxidation. This configuration enhances the electron transfer with Li2S6, where the electrons tend to aggregate between P and Li atoms as two separate parts rather than a single merged zone as observed in symmetric Co-N4 SACs. This process facilitates polysulfide decomposition and promotes Li2S nucleation/oxidation. Furthermore, the CoPNC interlayer effectively suppresses cell self-discharge and Li anode corrosion due to polysulfide shuttling. Li-Li symmetrical cell incorporated with the CoPNC interlayer achieves a prolonged lifespan exceeding 1000 h, and Li-S full cell delivers a discharge capacity of more than 1500 mAh g−1. This research provides insights into how the geometric configuration of SACs influences the performance of conversion-type batteries.